Evidence for the Role of Metabotropic Glutamate (mGlu)2 Not mGlu3 Receptors in the Preclinical Antipsychotic Pharmacology of the mGlu2/3 Receptor Agonist (–)-(1 R, 4 S,5 S,6 S)-4-Amino-2-sulfonylbicyclo[3.1.0]hexane-4,6-dicarboxylic Acid (LY404039) - Fell, Matthew J.; Svensson, Kjell A.; Johnson, Bryan G.; Schoepp, Darryle D. (The Journal of pharmacology and experimental therapeutics, 2008)
(–)-(1 R, 4 S,5 S,6 S)-4-Amino-2-sulfonylbicyclo[3.1.0]hexane-4,6-dicarboxylic acid (LY404039) is a potent and selective group II metabotropic glutamate [(mGlu)2 and mGlu3] receptor agonist for which its prodrug LY2140023 [(1 R,4 S,5 S,6 S)-2-thiabicyclo[3.1.0]-hexane-4,6-dicarboxylic acid,4-[(2 S)-2-amino-4-(methylthio)-1-oxobutyl]amino-, 2,2-dioxide monohydrate] has recently been shown to have efficacy in the treatment of the positive and negative symptoms of schizophrenia. In this article, we use mGlu receptor-deficient mice to investigate the relative contribution of mGlu2 and mGlu3 receptors in mediating the antipsychotic profile of LY404039 in the phencyclidine (PCP) and d- amphetamine (AMP) models of psychosis. To further explore the mechanism of action of LY404039, we compared the drugs’ ability to block PCP-induced hyperlocomotion to that of atypical antipsychotics in wild-type and mice lacking mGlu2/3 receptors. In wild-type animals, LY404039 (3–30 mg/kg i.p.) significantly reversed AMP (5 mg/kg, i.p.)-induced increases in ambulations, distance traveled, and reduced time spent at rest. LY404039 reversed PCP (7.5 mg/kg i.p.)-evoked behaviors at 10 mg/kg. The antipsychotic-like effects of LY404039 (10 mg/kg i.p.) on PCP and AMP-evoked behavioral activation were absent in mGlu2 and mGlu2/3 but not in mGlu3 receptor-deficient mice, indicating that the activation of mGlu2 and not mGlu3 receptors is responsible for the antipsychotic-like effects of the mGlu2/3 receptor agonist LY404039. In contrast, the atypical antipsychotic drugs clozapine and risperidone inhibited PCP-evoked behaviors in both wild-type and mGlu2/3 receptor-deficient mice. These data demonstrate that the antipsychotic-like effects of the mGlu2/3 receptor agonist LY404039 in psychostimulant models of psychosis are mechanistically distinct from those of atypical antipsychotic drugs and are dependent on functional mGlu2 and not mGlu3 receptors.